Study of the wheel eccentric load mechanism in hydraulic engineering vehicles and improvement measures - LIU Jiahui; HUANG Zhihui; YU Hongda; TIAN Mingjie (机车电传动)
Wheel eccentric load is commonly observed in driven hydraulic engineering vehicles and seriously impacts their operational safety. To address this issue, a dynamic model that accounts for the drive system was established for an engineering vehicle using SIMPACK software. This model was employed to analyze the variation patterns of wheel eccentric load in relation to tractive force and the corresponding effect on the rate of wheel load reduction. Subsequently, the influence of torque transmitted by the cardan shaft on the wheel loads of both sides was examined. Additionally, a calculation model for wheel eccentric load was established in MATLAB software for further theoretical analysis, which revealed the underlying mechanism of wheel eccentric load and facilitated structural modifications aimed at mitigating this imbalance. The results confirmed the presence of wheel eccentric load in hydraulic engineering vehicles under driving conditions. Specifically, for the No.1 and No.4 wheelsets, the left wheel load increased while the right wheel load decreased. In contrast, for the No.2 and No.3 wheelsets, the right wheel load increased while the left wheel load decreased. Wheel eccentric load amplified the maximum rate of wheel load reduction by 19.68%, indicting a detrimental effect on the operational safety of the engineering vehicle. Moreover, torque transmitted by the cardan shaft was identified as a contributor to wheel eccentric load, with the direction of torque rotation influencing either an increase or decrease in wheel load, and the magnitude of torque correlating with the extent of wheel eccentric load. The simulation results were in good agreement with the model-based calculations, fully demonstrating the rationality of the analyses. Compared to the original vehicle, the modified engineering vehicle resulted in wheel eccentric load of up to 3.41 kN, reflecting a reduction of up to 83.57%, without any noticeable change in axle load transfer, along with a 27.71% decrease in the rate of wheel load reduction. These results prove the modification is effective in reducing the degree of wheel eccentric load. The research findings can provide a theoretical reference for improving the safety of hydraulic engineering vehicles.